2022
DOI: 10.21608/aimj.2022.137902.1942
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Of Left Ventricular Systolic Function By Speckle Tracking Echocardiography In Young Hypertensive Patients

Abstract: Background: Tissue Speckle Tracking examines speckle aberrations in an echo picture to determine myocardial contractility and relaxation. Reflections, refraction, and dispersion of echo beams generate speckles. Aim of the study: The purpose of this research was to use speckled tracking echocardiography to identify subclinical left ventricular failure in young hypertension individuals who had normal systolic function by 2D echocardiography. Patients and Methods: The research included 30 hypertensive patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…Desai et al [7] conducted a study in adult hypertrophic cardiomyopathy (HCM) with normal LVEF (55%) and found that with patients with LVGFI less than 37% had a primary event versus those with LVGFI more than 37% [8%]. Sa velocity either septal, lateral, and average had the lowest mean value in G3 in agreement with our study Gab Allah et al [17] found that Sa velocity decreased in hypertensive cases than the control. In disagreement with our study, Ayoub et al [16] found no difference between his group studies as regard Sa wave; this discrepancy with our study may be due to different group design according to global longitudinal strain (GLS) and his study included hypertensive patients only.…”
Section: Resultssupporting
confidence: 88%
“…Desai et al [7] conducted a study in adult hypertrophic cardiomyopathy (HCM) with normal LVEF (55%) and found that with patients with LVGFI less than 37% had a primary event versus those with LVGFI more than 37% [8%]. Sa velocity either septal, lateral, and average had the lowest mean value in G3 in agreement with our study Gab Allah et al [17] found that Sa velocity decreased in hypertensive cases than the control. In disagreement with our study, Ayoub et al [16] found no difference between his group studies as regard Sa wave; this discrepancy with our study may be due to different group design according to global longitudinal strain (GLS) and his study included hypertensive patients only.…”
Section: Resultssupporting
confidence: 88%